PENGARUH INDEPENDENSI AUDITOR, RESIKO AUDIT TERHADAP KUALITAS HASIL AUDIT DENGAN MOTIVASI AUDITOR SEBAGAI VARIABEL PEMODERASI (Studi Empiris pada Auditor Eksternal KAP di Jakart a yang tidak terdaftar di Badan Pemeriksa Keuangan Republik Indonesia) - YA’ATULO WARAE (LPPM Universitas Nias Raya, 2018)
Results of the analysis of the CFA was invalid constructs X1: Independence Auditor; X2: Risk Audit; X3: Motivation Auditor as variable moderated and Y: Quality of Audit Result have been valid and reliability above 0.60 (ideally above 0.70) required. This research contains the five hypotheses. Of the five proposed hypothesis, there is one hypothesis was rejected. The results of testing this hypothesis suggests that the independence of the auditor has the value significance of 4.92 and risk audit with a fairly high significance value of varibel in this research is 5.03 which means significantly influence the quality of the audit results. While the variable moderated has only influence the motivation of the auditor that the value is negative and not significant to the quality of audit results. Results of auditor varibel moderated X1X3 motivation with variable Y can not moderate both the variable with the results rejected because hypotheses only 0.20, so make weaken the relationship of causality between the variables, this does not meet the criteria as a means moderated, but the others case the variable X2X3 to the moderated variable Y, which can be a tool of moderation between the two variable with the result of 2,51, meaning it can strengthen both the variables. Keywords : Independence Auditor, Audit Risk, Motivation Auditor, Quality Of Audit Results, Variable Moderated.